Modern possibilities of surgical treatment of benign breast tumors with ptosis: comparative analysis and long-term outcomes - R. M. Shabaev; I. V. Kolyadina; D. A. Blagovestnov; P. M. Starokon (Опухоли женской репродуктивной системы, 2025)
Aim. To evaluate the effectiveness of a new method for removing multiple benign breast tumors through a single access with subsequent correction of ptosis using a hemispherical glandular flap in comparison with bilateral sectoral resection of the mammary glands.Materials and methods. A prospective observational study was conducted involving 154 patients with benign breast tumors who were treated from 2022 to 2024. The patients were divided into two groups depending on the type of surgery performed: group I included 78 women with removal of multiple breast tumors through a single surgical access with subsequent correction of ptosis using a hemispherical glandular flap, group II included 76 patients with bilateral sectoral resection of the mammary glands. A comparative analysis of these types of surgical treatment of benign breast tumors was performed, and the quality of life of the patients before surgery and one year after surgical treatment were assessed.Results. When comparing the early postoperative period, no significant differences were found between the new method of removing multiple breast tumors through a single surgical access with subsequent correction of ptosis with a hemispherical glandular flap and bilateral resection of the mammary glands in terms of the number of hospital days, pain syndrome and sensitivity of the nipple-areolar complex. Carrying out surgical treatment with one-stage correction of ptosis allowed all patients to achieve a good long-term aesthetic result, avoid asymmetry, gross deformation of the mammary glands, while in group 2, 71 % of patients had aesthetic defects after surgery,  p<0.001. Evaluation of the mental component of quality of life one year after surgery showed a significant advantage of performing surgical treatment in group 1 compared to that in group 2, p < 0.001, which is most likely due to the removal of multiple breast tumors with simultaneous elimination of mammary ptosis, which had a positive effect on the psychoemotional state and quality of life of women.Conclusion. Our results prove the high efficiency and advantage of a new surgical method for removing multiple benign breast tumors through a single approach with subsequent correction of ptosis with a hemispherical glandular flap in terms of immediate surgical and long-term aesthetic results and improving the quality of life of patients.